Impact assessment of the ITM vaccine against East Coast Fever in Tanzania (ITM4Impact) - Farmer Survey - Kiara, Henry Kimathi; Teufel, Nils; Korir, Luke; Hammond, James; Wijk, Mark T. van (2024)
Impact assessment of the ITM (Infection & Treatment Method) vaccine against East Coast Fever in Tanzania. Farm-level cross-sectional survey of 994 cattle keepers categorised by ITM adoption status.